The importance of mathematic in industry - Nor Salwana, Mohammad Idris (2017)
For the first time since its inception, Faculty of Industrial Sciences & Technology (FIST) together with Institut Teknologi Sepuluh Nopember (ITS), Society for Industrial and Applied Mathematics (SIAM), Persatuan Sains dan Matematik (PERSAMA) and Malaysia Statistic Institute (ISM) organized an International Conference on Applied & Industrial Mathematics and Statistics 2017 (ICoAIMS 2017), held at Vistana Hotel, Kuantan recently.